HUBUNGAN POLA SARAPAN DENGAN STATUS GIZI DAN PRESTASI BELAJAR PADA ANAK SEKOLAH DI SD NO 1 PEREAN,BATURITI,TABANAN, BALI - made tika kasmuri; Desak Putu Sukraniti; I.G.A Ari Widarti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Breakfast is food that is eaten every morning or an important activity is carried out before filling in other activities every day. Breakfast is needed to fill the empty stomach for 8-10 hours and is useful in improving learning concentration and physical abilities. The food must contain all the nutrients needed by the body. Food with this balanced composition is needed because the body needs nutrients for growth, development and maintenance. Nutritional status is a reflection of the balance state of nutritional intake (intake) and the needs (requirements) of nutrients in the form of certain variables. The purpose of this study was to determine the relationship of breakfast patterns with nutritional status and learning achievement in school children at SD No. 1 Perean. This type of research was observational with a crossectional research design. The sample size in this study is 75. Data collection uses identity forms, 24-hour recall method, measurement of body weight and height. Data is processed by spearman analysis. The results showed that 1.3% of school children with breakfast patterns were rare, 16% with occasional categories and 82.7% with frequent categories. The nutritional status of school children is 54.7% with normal nutritional status, 21.3% with nutritional status fat, 24% with nutritional status obesity. The learning achievement of Perean Elementary School No. 1 children is 1.3% with sufficient achievements and 98.7% with good achievements. There is no relationship between breakfast habits, breakfast type, breakfast energy consumption level, consumption level of breakfast protein with nutritional status. There is a relationship between breakfast habits and learning achievement. There is no relationship between the type of breakfast, the level of energy consumption of breakfast, the level of consumption of protein breakfast with learning achievement. There is no relationship between nutritional status and learning achievement. Keywords: breakfast, nutritional status, learning achievement